2014
DOI: 10.1097/aog.0000000000000381
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Age at Diagnosis of Endometrial Cancer

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
64
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(75 citation statements)
references
References 15 publications
8
64
1
2
Order By: Relevance
“…Our analysis demonstrates that nonendometrioid endometrial cancer rates have shown the greatest incidence rate increases over the last decade, supporting Wartko and colleagues in their conclusion that obesity is contributing to, but not solely responsible for, the rising incidence rates of endometrial cancer (2). In addition, it is possible that obesity is associated with an earlier age of onset, particularly for endometrioid cancers (40). Continued surveillance of this issue, also considering morbidity and mortality, is warranted.…”
Section: Discussionsupporting
confidence: 76%
“…Our analysis demonstrates that nonendometrioid endometrial cancer rates have shown the greatest incidence rate increases over the last decade, supporting Wartko and colleagues in their conclusion that obesity is contributing to, but not solely responsible for, the rising incidence rates of endometrial cancer (2). In addition, it is possible that obesity is associated with an earlier age of onset, particularly for endometrioid cancers (40). Continued surveillance of this issue, also considering morbidity and mortality, is warranted.…”
Section: Discussionsupporting
confidence: 76%
“…3 In addition, increasing rates of obesity appears to be contributing to higher rates of endometrial cancer in the younger age population as well. 5 Many patients who have undergone hysterectomy for endometrial or early-stage cervical cancer require postoperative pelvic radiotherapy with a number of randomized trials showing improvements in local control and progression free survival. 6 To reduce surrounding normal tissue dosing and overall short-term and long-term side effects from treatment, radiation oncologists have transitioned away from conventional external beam plans with large treatment fields and have trended to more conformal plans.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, Reeves et al predicted that up to 51 % of endometrial cancer cases could be attributable to obesity (Reeves et al 2007). Nevadunsky et al report a strong correlation between obesity and younger age at diagnosis, and Duska et al found that women aged 24-40 years and BMI >30 were associated with stage I, grade I disease (Duska et al 2001;Nevadunsky et al 2014). In general, obesity induces a hyperestrogenic state due to the conversion of adrostenedione to estrone in peripheral adipose tissue.…”
Section: Obesity and Endometrial Cancermentioning
confidence: 93%